Handbook of research on global hospitality and tourism management - Camillo, Angelo, 1954- (Hershey, PA: Information Science Reference, 2015)
'This book contributes to the body of knowledge on travel and tourism by presenting a global view of the hospitality industry, including theoretical research into industry trends as well as case studies from around the world'--
Includes bibliographical references and index.
Keywords: Tourism -- Research -- Methodology; Hospitality industry -- Research